Review Study of E-Voting System Based on Smart Contracts Using Blockchain Technology - Jumaa, Maral Hassan; Shakir, Ahmed Chalak (Iraqi Journal of Science, 2023)
Voting is an important procedure in democratic societies in different countries, including Iraq. Electronic voting (E-voting) is becoming more prevalent due to reducing administrative costs and burdens. E-voting systems have many restrictions that affect the electoral process. For example, fraud, tampering with ballot boxes, taking many hours to announce results, and the difficulty of reaching polling stations. Over the last decade, blockchain and smart contract technologies have gained widespread adoption in various sectors, such as cryptocurrencies, finance, banking, and most notably in e-voting systems. If utilized properly, the developer demonstrates properties that are promising for their properties, such as security, privacy, transparency, and decentralization. Moreover, these technologies allow citizens to vote wherever they are via digital technology (computers, smartphones). This paper explains the nature of blockchain and smart contracts and systematically reviews several important e-voting studies. Comparative analysis is conducted on recent related papers in the last five years (published in highly ranked journals and international conferences) regarding blockchain types, frameworks, security requirements, and the implemented algorithms.